Evolution of an Early Illness Warning System to Monitor Frail Elders in Independent Living. Issue 3 (2nd September 2011) - Alexander, Gregory L.; Rantz, Marilyn; Skubic, Marjorie; Koopman, Richelle J.; Phillips, Lorraine J.; Guevara, Rainer D.; Miller, Steven J.
Abstract : This paper describes the evolution of an early illness warning system used by an interdisciplinary team composed of clinicians and engineers in an independent living facility. The early illness warning system consists of algorithms which analyze resident activity patterns obtained from sensors embedded in residents' apartments. The engineers designed an automated reasoning system to generate clinically relevant alerts which are sent to clinicians when significant changes occur in the sensor data, for example declining activity levels. During January 2010 through July 2010, clinicians and engineers conducted weekly iterative review cycles of the early illness warning system to discuss concerns about the functionality of the warning system, to recommend solutions for the concerns, and to evaluate the implementation of the solutions. A total of 45 concerns were reviewed during this period. Iterative reviews resulted in greater efficiencies and satisfaction for clinician users who were monitoring elder activity patterns.